Comparison of Bottomless Lift Nets and Breder Traps for Sampling Salt‐Marsh Nekton. Issue 1 (31st December 2015) - Raposa, Kenneth B.; Chintala, Marnita
Abstract: Vegetated salt‐marsh surfaces provide refuge, forage, and spawning habitat for estuarine nekton, yet are threatened by accelerating rates of sea‐level rise in southern New England and elsewhere. Nekton responses to ongoing marsh surface changes need to be evaluated with effective and quantitative nekton sampling gear. The goal of this study was to evaluate the effectiveness of different gear for monitoring nekton in emergent salt‐marsh vegetation by comparing nekton parameters between Breder traps and bottomless lift nets and between Breder traps made from different materials. Breder traps collected a significantly different nekton community, fewer species, and larger‐sized Mummichogs Fundulus heteroclitus than did lift nets. Nekton community composition, richness, and the size of green crabs Carcinus maenas also differed significantly between Breder traps constructed from acrylic and wire mesh. These results show that it is not appropriate to directly compare nekton data between Breder traps and lift nets, nor between Breder traps made from different materials. Our lift‐net data correspond well to other data collected with enclosure traps in southern New England. We recommend lift nets or similar enclosure traps for sampling nekton in emergent marsh vegetation and caution against using Breder traps in monitoring and assessment programs.